2014
DOI: 10.2147/ccid.s74411
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiofrequency in cosmetic dermatology: focus on nonablative treatment of acne scars

Abstract: Acne is a common affliction among many teens and some adults that usually resolves over time. However, the severe sequela of acne scarring can lead to long-term psychological and psychiatric problems. There exists a multitude of modalities to treat acne scars such as more invasive surgical techniques, subcision, chemical peels, ablative lasers, fractional lasers, etc. A more recent technique for the treatment of acne scars is nonablative radiofrequency (RF) that works by passing a current through the dermis at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 21 publications
1
57
0
1
Order By: Relevance
“…2 A similar pattern of optimal results is seen at approximately 3 months after final treatment. Side effects are similar with transient erythema, edema, burning, and pain being the most common.…”
mentioning
confidence: 53%
“…2 A similar pattern of optimal results is seen at approximately 3 months after final treatment. Side effects are similar with transient erythema, edema, burning, and pain being the most common.…”
mentioning
confidence: 53%
“…The technology of bipolar fractionated RF allows the current to pass between skin and electrodes in a controlled way. It generates a fractionated heating in deep dermis, stimulating dermal remodeling, collagen contraction and fibroblast stimulation with little epidermal damage [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this technology allows the combination of techniques in one, so that there is a greater stimulus to the skin remodeling [17].…”
Section: Discussionmentioning
confidence: 99%
“…For acne scarring, a moderate improvement of 25% to 75% can be expected after 3 to 4 treatment sessions with FRF. 92 Numerous studies on the use of FRF for acne scarring in darker skin types have shown it to be effective, with a relatively low risk of PIH. [93][94][95] While moderate improvement in acne scarring is possible, it remains to be seen how FRF compares to more well-established treatments, such as AFL.…”
Section: Fractional Radiofrequencymentioning
confidence: 99%
“…99 Common adverse reactions associated with FRF and RFM include transient pain, erythema, edema, and scabbing that resolve within 3 to 5 days. 92,95,107 Prolonged erythema, edema, and purpura are rarely seen. Rare instances of acne exacerbations 93 and HSV outbreaks 96 have been reported.…”
Section: Fractional Radiofrequencymentioning
confidence: 99%